1999
DOI: 10.1246/cl.1999.219
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Epithio Groups of p-tert-Butylthiacalix[4]arene in a Zn2+ Complex Studied by X-Ray Crystallography

Abstract: Single-crystal X-ray analysis has shown that p-tert-butylthiacalix[4]arene (H4L) binds to Zn2+ ion by bridging sulfur atoms in addition to phenolic oxygen atoms to form [Zn4L(H2L)2].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
2
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 3 publications
1
49
2
1
Order By: Relevance
“…They possess several interesting features, the most remarkable being an ability to form very stable metal complexes without a modification to their upperand/or lower-rims. [6][7][8][9] With conventional calix[n]arenes, it is necessary to modify the upper-and/or lower-rims with suitable functional groups to prepare stable metal complexes. [10][11][12][13] Because of these features, some thiacalix[n]-arene derivatives have been used as an analytical reagent for the separation of various metal ions.…”
mentioning
confidence: 99%
“…They possess several interesting features, the most remarkable being an ability to form very stable metal complexes without a modification to their upperand/or lower-rims. [6][7][8][9] With conventional calix[n]arenes, it is necessary to modify the upper-and/or lower-rims with suitable functional groups to prepare stable metal complexes. [10][11][12][13] Because of these features, some thiacalix[n]-arene derivatives have been used as an analytical reagent for the separation of various metal ions.…”
mentioning
confidence: 99%
“…Much attention has been focused on the characteristics of thiacalix[n]arenes for forming stable metal complexes without modifying their upperand/or lower-rims with functional groups. [10][11][12][13] We have recently found that Fe 3+ -thiacalix [4]arenetetrasulfonate on the modified anion-exchanger (Fe 3+ -TCAS [4]A-500) exhibited very strong peroxidase-like catalytic activity, and was useful as a peroxidase mimetics. 14 Moreover, we have developed new methods for the spectrophotometric determination of hydrogen peroxide using the peroxidase-like catalytic activity of Fe 3+ -TCAS [4]A-500, and applied them to measurements of glucose and uric acid.…”
mentioning
confidence: 99%
“…It may be reasonable that the Fe 3+ ion is coordinated to the -S-of the epithio groups and the phenolic oxygen atoms of TCAS. According to an X-ray analysis of a Zn 2+ complex of p-tbutylthiacalix [4]arene by Iki et al, 22 actually, the Zn 2+ ion was coordinated to the -S-of the epithio groups and the phenolic oxygen atoms. In the case of Fe 3+ -TCAS on a modified anionexchanger, similarly, the -S-of the epithio groups and the phenolic oxygen atoms of TCAS may be responsible for coordination to the Fe 3+ ion.…”
Section: Resultsmentioning
confidence: 99%